We will rock our classmates - Higgins, Ryan T. (Los Angeles : Disney/Hyperion, 2020)
As the only T. rex in her school, Penelope is often overlooked but when she loses her confidence after signing up for the school talent show, her father and some friends help her find her courage.
School Library Journal starred, May 2020
K-3
AD540L
Keywords: Tyrannosaurus rex -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Talent shows -- Juvenile fiction; Self-confidence -- Juvenile fiction; Schools -- Juvenile fiction; Humorous stories; Tyrannosaurus rex -- fiction; Dinosaurs -- Fiction; Talent shows -- Fiction; Self-confidence -- Fiction; Schools -- Fiction; Humorous stories; Humorous fiction; Animal fiction